Polish Independent Press Review, no. 13 (1986) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Topical reviews of Polish samizdat publications in English prepared by RFE staff members to be used by different national broadcasting units. PIPR was published from 1986 until November 1989 as a continuation of Polish Underground Extracts (PUE). The Opposition After the Amnesty. Polish Opposition Views on the Reasons for the Amnesty / by Anna PomianThe release of Poland's political prisoners, although welcomed by the opposition, has been interpreted as a basically tactical maneuver on the part of the authorities. Extensive comments on possible motives behind the amnesty have appeared in the unofficial press; they reflect the views of leading independent publications and prominent opposition figures. The Future Shape and Function of Solidarity's Underground Structures / by Anna PomianRecent attempts at open activity by the democratic opposition have not eliminated the need for covert activity. Underground Solidarity structures that have existed since the imposition of martial law on 13 December 1981 are likely to continue to play both supportive and tactical roles in the future strategy of the opposition movement. The Possibility of Overt Activity for the Democratic Opposition / by Nika KrzeczunowiczThe official announcement of the release of political prisoners prompted a series of statements about how a future relationship between the authorities and the opposition could be forged. Solidarity Embarks on a New Strategy / by Nika KrzeczunowiczFollowing the release of political prisoners, many underground publications offered editorial comments and interviews with opposition leaders about what the next moves should be in dealing with the new situation. A Lesson on Dialogue, or How the Authorities Questioned 3,000 Activists / by Anna PomianWhen General Czesław Kiszczak announced the release of political prisoners, he also said that his security services had questioned more that 3,000 political activists and warned them against continuing their activities. The independent press has published details about the actual scope and content of these interviews.